PENGARUH ZAKAT TERHADAP PENGENTASAN KEMISKINAN UMAT - Wijayanti (UNIBA Surakarta), Anita; Hendrik, Hendrik (Manajemen Bisnis Syariah, 2011)
Giving or obtain cash for zakat which its realization with the expenditure estae(in the form shodaqoh, infaq, and religious obligatory) and rights of fitrah bodyamong by sholat, to work exercise sport, marrying, and so on) for fellow beingimportance, real correctly, istigomah, and candid in the reality represent one ofsolution most precise and especial [is] which have been specified by Alloh and Rosul.Mean the word of zakat according to Ianguage method (etimologis) a holymatter soul/liver (tazkiyatun nufuz) and estae owned by every human being.Mean thezakat according to syari in general (referred also religious obligatory mutlaq / public) is rights owned by each;every human being which is obliged to be gived or obtaincash for (tobe shodaqoh) according to rule of Alloh and rosul-Nya which shohih /hasan, what is generally released goodness in the form of reality (riil) and also in theform of not reality ( abstraction), with not limited by stipulating prosentase (nishob)and time / annual rotation (haul) (so that cash shodaqoh depended from ridho the itsowner). what in the end addressed to increase feel the silaturahim (brotherhood andassociation) and kemaslahatan (happines) among fellow being, and ever look for theridho and/ taqorrub (to close) of GoodMean the religious obligatory according to syari peculiarly (referred alsoreligious obligatory muqoyyad / special) a matter which deal with gift some of certainestae, owned by every human being, what obliged to be gived or obtain cash for (to beshodaqoh) as according to nishob-nya and have reached the haul od Good accordingto rule of Alloh and rosul which shohih / hasan candidly (only hope the ridho of Good),to a group of certain people (among other things, poor family, or which likely, besidesBani Hasyim and socioeconomic Bani Mutholib).From method, fadhillah (hikmah)and benefit which can be taken by syariat zakat mutlaq (in general) and muqoyyad(peculiarly) its mean break various solution for help tobe good conditions of poornessin society, where about by shodaqoh and the religious obligatory expected bydeductible Impecunious [through/ passing] prows of transfer estae from plutocratpeoplekey words: zakat, impecunious